ANALISIS MAKNA PUISI â€œLANSKAPâ€ KARYA SAPARDI DJOKO DAMONO - Ani Hidayanti; Teti Sobari (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Literary work is an expression that is created based on the thoughts, experiences, and feelings of the author. Literary works that are in great demand and read are poetry. Poetry is an interesting literary work to study because it contains an implied meaning. This allows for different interpretations of each reader. Therefore, in this study the author is interested in analyzing meaning, namely analyzing the implied meaning contained in the poem "Lanskap" by Sapardi Doko Damono. This study aims to (1) analyze the implied meaning contained in the poem entitled "Lanskap" (2) describe the results of the poetry analysis that has been studied. This study uses a descriptive method in which the author describes or tells the poem being studied. The poem "Lanskap" is studied and discussed to obtain the meaning implied in this poem so that it can be conveyed to the reader. The poem "Lanskap" has that in a relationship there must be loyalty in order to continue to maintain the integrity of the relationship. Time cannot be a reason for someone to stop being faithful.